The cardioprotective effects of HTK solution and conventional blood cardioplegia in patients with atrial fibrillation undergoing valvular replacement and Cox maze III procedure - BingMei Qiu; Lei Zhang; Dan Wu; Qian Li; Lei Sun; AnLi Wang; Zhilong Xi; HaiWei Wu; ChangTian Wang; ShanWu Feng (Journal of Cardiothoracic Surgery)
Abstract Introduction The study was to assess the myocardial protection effects of the histidine-tryptophan-ketoglutarate (HTK) solution and the 4:1 blood cardioplegia (BC) in patients with atrial fibrillation (AF) who were subjected to valvular replacement concomitant with the Cox maze III surgery. Methods A cohort of 148 individuals afflicted with AF, who received valve replacement surgery in conjunction with the Cox maze III procedure at our clinic within the period extending from 2015 to 2023, were enrolled. Subsequent to adjustment by propensity score matching (PSM), the patients were categorized into two distinct groups: the HTK group and the BC group. The primary end points assessed inotropic support requirements, complications, troponin trend, mechanical ventilation time and the intensive care unit stay. Arrhythmias, aortic cross-clamp and cardiopulmonary bypass times, and other clinical perioperative variables were considered as secondary end points. Results No substantive disparities were observed concerning mortality rates, arrhythmias, neurological events, or renal complications. The duration of cardiopulmonary bypass and the aortic cross-clamp time did not demonstrate any marked variations between both groups, with p-values of 0.71 and 0.05, respectively. The time required for weaning from mechanical ventilation and the length of postoperative hospitalization were notably less in the group receiving HTK solution (p < 0.001 and p = 0.03, respectively). While inotropic support need was higher in the BC group (p = 0.02). Conversely, the dosage and frequency of perfusions were considerably increased in the BC group (p < 0.001 for each parameter). Within subgroups stratified by longer than 150 min of aortic cross-clamping duration, those in the BC cohort had significantly elevated peaks of cardiac troponin I (cTnI) (p = 0.01), whereas individuals in the HTK group experienced less mechanical ventilation time (p = 0.002) and shorter durations of intensive care unit admission (p < 0.001). The LVEF value in the HTK group was higher compared to that in the BC group in the 3-month follow-up data (p = 0.02). Conclusions Both the HTK and 4:1 blood cardioplegia could be used safely in patients with AF who were subject to valvular replacement and Cox maze III procedure. However, the utilization of HTK conferred a greater advantage in diminishing the duration of mechanical ventilation weaning and the duration of postoperative hospitalization. HTK may be a better myocardial protection in patients with long cross-clamp time. The follow-up data indicated that HTK might be superior to 4:1 blood cardioplegia in the short-medium term cardiac function.